Pengetahuan dan Perilaku Vulva Hygiene dapat Menurunkan Angka Kejadian Keputihan pada Remaja Putri: Knowledge and Behavior of Vulva Hygiene Can Reduce the Incidence of Vaginal Discharge in Young Women - Falsamawarti Waruwu; Ahmad Rizal; Emi Yuliza (Dohara POAJ, 2021)
Introduction: Leucorrhoea is an early symptom of almost all types of diseases of the female reproductive organs. Methods: The research design used in this study is research correlational. The approach used in this research is cross sectional. The sampling technique used a sampling technique with a total sampling of 40 respondents. The instrument used is to use a questionnaire by distributing links via google form. Results: From the results of univariate data testing, it was found that the frequency distribution of knowledge was less than 65%, and knowledge was good with a percentage of 35%. Distribution of 50% bad behavior, and 50% percentage of good behavior. From the results of the bivariate data, it was found that there was a relationship between knowledge and behavior of Vulva Hygiene with the incidence of vaginal discharge with ρ-value 0,000. Discussion: From the results of the research that has been collected, it can be concluded that there is a relationship between knowledge, and behavior of Vulva Hygiene with the incidence of vaginal discharge in adolescent girls.